2011
DOI: 10.12968/jowc.2011.20.5.242
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy of a new monoflament fibre-containing wound debridement product

Abstract: The evaluation protocol was proposed and supported by Lohmann & Rauscher GmbH, who provided the evaluation products. MS and MA are employees of Lohmann & Rauscher. The other authors declare to have no relevant financial interest in the evaluation. Apart from input to the protocol, the sponsors had no role in the conduct of the study, such as data collection, analysis, or preparation, review, or approval of the manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 9 publications
0
18
0
Order By: Relevance
“…An effective method is required that can be handled by all wound care clinicians in all settings [12,13]. It should be easy to perform, safe, and, importantly, comfortable for patients [5,13]. In a clinical study the debridement pad was shown to effectively remove devitalized tissue [5].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…An effective method is required that can be handled by all wound care clinicians in all settings [12,13]. It should be easy to perform, safe, and, importantly, comfortable for patients [5,13]. In a clinical study the debridement pad was shown to effectively remove devitalized tissue [5].…”
Section: Discussionmentioning
confidence: 99%
“…It should be easy to perform, safe, and, importantly, comfortable for patients [5,13]. In a clinical study the debridement pad was shown to effectively remove devitalized tissue [5]. The authors concluded that the results of the clinical evaluation indicate that the monofilament fiber product has the potential to replace several modes of debridement, based on its efficacy, short procedure, ease of use, and patient comfort [5].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…13 Recently, new, mechanical, polymer fiber debriding devices have emerged, designed to remove both established wound biofilms and devitalized tissue with minimal discomfort ( e.g. , Debrisoft ® ; Activa Healthcare, Debrimitt ™ ; Crawford Healthcare Ltd. 14 ).…”
Section: Clinical Problem Addressedmentioning
confidence: 99%